Multiple pathways from the neighborhood food environment to increased body mass index through dietary behaviors: A structural equation-based analysis in the CARDIA study. (November 2015) - Richardson, Andrea S.; Meyer, Katie A.; Howard, Annie Green; Boone-Heinonen, Janne; Popkin, Barry M.; Evenson, Kelly R.; Shikany, James M.; Lewis, Cora E.; Gordon-Larsen, Penny
Abstract: Objectives: To examine longitudinal pathways from multiple types of neighborhood restaurants and food stores to BMI, through dietary behaviors. Methods: We used data from participants ( n =5114) in the United States-based Coronary Artery Risk Development in Young Adults study and a structural equation model to estimate longitudinal (1985–86 to 2005–06) pathways simultaneously from neighborhood fast food restaurants, sit-down restaurants, supermarkets, and convenience stores to BMI through dietary behaviors, controlling for socioeconomic status (SES) and physical activity. Results: Higher numbers of neighborhood fast food restaurants and lower numbers of sit-down restaurants were associated with higher consumption of an obesogenic fast food-type diet. The pathways from food stores to BMI through diet were inconsistent in magnitude and statistical significance. Conclusions: Efforts to decrease the numbers of neighborhood fast food restaurants and to increase the numbers of sit-down restaurant options could influence diet behaviors. Availability of neighborhood fast food and sit-down restaurants may play comparatively stronger roles than food stores in shaping dietary behaviors and BMI. Highlights: We examine longitudinal pathways from food environment to BMI through diet behaviors. Access to restaurants was related to consumption of a fast food-type diet. Access to food stores was inconsistently associated with BMI through diet pathways.